2004
DOI: 10.1242/jcs.01531
|View full text |Cite
|
Sign up to set email alerts
|

Tau interaction with microtubules in vivo

Abstract: Tau is a major microtubule-associated protein which induces bundling and stabilization of axonal microtubules (MTs). To investigate the interaction of tau with MTs in living cells, we expressed GFP-tau fusion protein in cultured Xenopus embryo neurons and performed time-lapse imaging of tau-labeled MTs. Tau uniformly labeled individual MTs regardless of their assembly/disassembly status and location along the axon. Photobleaching experiments indicated that interaction of tau with MTs is very dynamic, with a ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
105
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 66 publications
16
105
1
Order By: Relevance
“…Although the C terminus of Ncd and kinesin-1 do have motor activity, and can induce MT movement, none of these proteins has two MT binding sites; thus, they are not able to bundle MTs. We also overexpressed in cells GFP-tau fusion protein (GFP-tau23; Samsonov et al, 2004), which has a high MT-bundling activity, but lacks a motor domain and therefore cannot move MTs against each other. Fluorescence microscopy analysis of MTs in the transfected cells showed that, as expected, overexpression of tau-GFP, but not other proteins, induced the formation of MT bundles (Supplemental Movies 5 and 6 and Supplemental Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the C terminus of Ncd and kinesin-1 do have motor activity, and can induce MT movement, none of these proteins has two MT binding sites; thus, they are not able to bundle MTs. We also overexpressed in cells GFP-tau fusion protein (GFP-tau23; Samsonov et al, 2004), which has a high MT-bundling activity, but lacks a motor domain and therefore cannot move MTs against each other. Fluorescence microscopy analysis of MTs in the transfected cells showed that, as expected, overexpression of tau-GFP, but not other proteins, induced the formation of MT bundles (Supplemental Movies 5 and 6 and Supplemental Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The gel-purified fragment was then digested with EcoR1/ BamH1 and ligated into EcoR1/BamH1-digested pEGFPN1 vector (Clontech, Mountain View, CA). GFP-tau plasmid (GFP-tau23;Samsonov et al, 2004) was a gift from Dr. Sergei Popov (University of Illinois at Chicago). …”
mentioning
confidence: 99%
“…Interestingly, tau accumulates at sites of microtubule bending, suggesting that it helps in preventing microtubule rupture (25). This could also be the role of the putative luminal protein in Apicomplexa, as a 1/8-nm −1 layer line could also be observed in the highly bent tubulin fi bers of the toxoplasma conoid (19).…”
Section: A Novel Molecule Binding At the Lumen Of The Microtubulesmentioning
confidence: 99%
“…MTs in axons have been found to be particularly densely decorated by tau proteins at regions of high curvature, suggesting an influence of the mechanical properties [319]. It was also hypothesized that tau has a protective function for MTs against the action of the MT-severing protein katanin [298].…”
Section: Modification Of Mts By Maps : the Example Of Tau Proteinsmentioning
confidence: 99%